Transition to Virtual Care Services during COVID-19 at Canadian Pain Clinics: Survey and Future Recommendations - Victoria Borg Debono; Samuel Neumark; Norman Buckley; Ramesh Zacharias; Eleni Hapidou; Jennifer Anthonypillai; Susy Faria; Carrie-Lynn Meyer; Thomas Carter; Nadia Parker; Brenda Lau; Emmanuel Abreu; et al. (Pain Research and Management)
Introduction. Due to the COVID-19 pandemic, healthcare centers quickly adapted services into virtual formats. Pain clinics in Canada play a vital role in helping people living with pain, and these clinics remained essential services for patients throughout the pandemic. This study aimed to (1) describe and compare the transition from in-person to virtual pain care services at Canadian pain clinics during the onset of the COVID-19 pandemic and (2) provide postpandemic recommendations for pain care services to optimize the quality of patient care. Materials and Methods. We used a qualitative participatory action study design that included a cross-sectional survey for data collection and descriptive analysis to summarize the findings. Survey responses were collected between January and March of 2021. The survey was administered to the leadership teams of 11 adult pain clinics affiliated with the Chronic Pain Centre of Excellence for Canadian Veterans. Responses were analyzed qualitatively to describe the transition to the virtual pain services at pain clinics. Results. We achieved a 100% response rate from participating clinics. The results focus on describing the transition to the virtual care, current treatment and services, the quality of care, program sustainability, barriers to maintaining virtual services, and future considerations. Conclusions. Participating clinics were capable of transitioning pain care services to the virtual formats and have in-person care when needed with proper safety precautions. The pandemic demonstrated that it is feasible and sustainable for pain clinics to have a hybrid of virtual and in-person care to treat those living with pain. It is recommended that moving forward, there should be a hybrid of both virtual and in-person care for pain clinics. Ministries of Health should continue to develop policies and funding mechanisms that support innovations aimed at holistic healthcare, interdisciplinary teams, and the expansion of clinics’ geographical reach for patient access.